DESCRIPTIVE ANALYSIS OF STUDENT’S SELF EFFICACY IN THE DISCOVERY LEARNING PROCESSES - Mufida, Husna Noor; Linuwih, Suharto; Sugianto, Sugianto (Universitas Negeri Semarang, 2019)
This research aims to describe the state of self efficacy on the application of learning discovery learning model on harmonic vibration topic. In addition to reveal the factors that influence the increase or decrease of students' self efficacy with the application of discovery learning model. This research is a qualitative descriptive analysis research. Discovery learning model is implemented in 38 students class X MIPA 2 of SMA 1 Bae Kudus. Data collection was done by giving questionnaires, observation, and interview. Questionnaire of student?s self efficacy also has been given to determine the condition of self efficacy of students before and after the learning process implemented. The results showed that the initial self efficacy condition of students who had low initial increase although not significant. The condition of early efficacy of students before the learning process determines the level of student success in the learning process. Analysis of the first time self efficacy of students with the low category can be used as an anticipation or prevent the final learning outcomes of students do not become low.